Development Model of Social Service Activities Management of College Students in Nan’an District, Chongqing, People’s Republic of China - Zurun, He; Jeewattana, Somsak; Pantachai, Pittaya (วารสารสันติศึกษาปริทรรศน์ มจร, 2026)
The objectives were: 1) to investigate the management elements of college students’ social service activities in Nan’an District, Chongqing; 2) to develop a development model for college students’ social service activities in Chongqing; 3) to evaluate the development model for college students’ social service activities in Nan’an District, Chongqing. The research methodology comprises 3 phases. Phase 1: studying the elements of college students’ social service activities. Content validity was assessed using IOC by 3 experts. Phase 2: constructing a development model for college students’ social service activities through interviews with administrators from 3 exemplary institutions. The panel of 5 experts validated the draft model. Phase 3: evaluating the model’s accuracy and applicability by 7 qualified experts, while assessing its feasibility and utility through feedback from 30 student union presidents. The results of the research were found to be: 1) The development model for college students’ social service activities in Nan’an District, Chongqing, China consists of 4 key elements: organizational leadership, support mechanism, institutional development, and professional development. 2) Developing an IPOS model for college students’ social service activities in Nan’an District, Chongqing, People’s Republic of China. Using the PDCA Cycle management philosophy as its theoretical framework. 3) The evaluation results of the development model for college students’ social service activities in Nan’an District, Chongqing, People’s Republic of China indicate that experts rated its accuracy and applicability at the highest level, while student union leaders rated its feasibility and utility at the highest level.